Energy Resource of Charcoals Derived from Some Tropical Fruits Nuts Shells - Damgou Mani Kongnine; Pali Kpelou; N’Gissa Attah; Saboilliè Kombate; Essowè Mouzou; Gnande Djeteli; Kossi Napo (International Journal of Renewable Energy Development, 2020)
This work was focused on carbonizing four tropical fruits shells wastes such as: coconut shells (CS), palmyra shells (PS), doum palm shells (DPS), whole fruit of doum palm (WFDP) and teak wood (TW) used as control. The aim was to investigate the potential of those biochar to be used as an alternative energy source in replacement ofcharcoal. The raw biomasses samples were carbonized under the same conditions and some combustion characteristics of the obtained biochar such as lower calorific value, energy per unit volume associated to bulk density, ash content, moisture content and ash mineral content were investigated. The temperature in the furnace was estimated during carbonization process using a K-type thermocouple. The thermal profile of the studied raw biomasses reveals three phases of carbonization. The biochar yield drops significantly for all biomasses as the final maximum temperature increases. The average yields obtained ranged from 37.81 % for palmyra shells to 27.57 % for the doum palm shells. The highest yield achieved was 42.32 % obtained at 280 °C for palmyra shells, the lowest yield (24.42 %) was recorded at the highest maximum temperature of 590 ° C for doum palm shells. The results of energy parameters of the studied biochar showed that coconut shells charcoal presented the highest lower calorific value (28.059 MJ.kg-1), followed by doum palm shells (26.929 MJ.kg-1) when, with 25.864 MJ.kg-1, whole fruit of doum palm charcoal showed the lowest lower calorific value. Similarly, with the highest bulk density of 0.625 g/cm3 coconut shells charcoal presented the highest energy per unit volume (17536.88 J/cm3), whereas with the lowest bulk density of 0.415 g/cm3, whole fruit of doum palm charcoal presented the lowest energy per unit volume. The ash content analysis showed that whole fruit of doum palm had the highest ash content (18.75 %) and palmyra nut shells charcoal (8.42 %).Teak wood charcoal, took as control, has the highest lower calorific value (32.163 MJ.kg-1), less dense as coconut shell (0.43 g/cm3), his energy per unit of volume is 13830.09 j/cm3 but the lowest value of as content (2.90 %). Among these biomasses charcoals, only whole fruit of doum palm charcoal ash showed a high chloride and sulfide content respectively  9.73 % and 1.75 % in weight. From these results, the produced charcoals could be used as alternative fuels except for whole fruits of doum palm charcoal which chloride and sulfide content were found high. ©2020. CBIORE-IJRED. All rights reserved